A semi‐analytical study of the MHD micropolar water‐based hybrid nanofluid flow over a stretching surface with variable heat source/sink. Issue 12 (11th October 2022) - Lone, Showkat Ahmad; Raizah, Zehba; Saeed, Anwar; Dawar, Abdullah; Galal, Ahmed M.; Kumam, Poom
Abstract: The industry level enhancement of the thermal conductivities of various base fluids is greatly aided by a nanofluid. Most engineering phenomena call for the removal of heat in order to improve industrial machinery performance. These fluids have a variety of uses, such as coolants for electric gadgets, car engines, heat exchangers and nuclear reactors. In this article, the authors have investigated the micropolar water‐based hybrid nanofluid containing silver and alumina nanoparticles over an extending surface. The flow problem also takes into account the Joule heating, variable heat source/sink, thermal radiation, chemical reaction, and activation energy. The flow problem is taken in the form of PDEs which are then transformed to ODEs by means of suitable similarity variables. The flow problem is solved with the help of HAM, which is capable of solving highly nonlinear partial and ordinary differential equations. The convergence of the HAM is also shown with the help of Figure 1. The results showed that the physical parameters have a greater influence on the velocity profile of nanofluid flow than hybrid nanofluid flow. However, the upshots of the physical constraints on the thermal profiles have a dominant impact on the hybrid nanoliquid flow relative to nanofluid. Also, it found that the physical parameters have a greater influence on the energy and mass transfer rates of the hybrid nanofluid flow than the nanofluid. Abstract : The industry level enhancement of the thermal conductivities of various base fluids is greatly aided by a nanofluid. Most engineering phenomena call for the removal of heat in order to improve industrial machinery performance. These fluids have a variety of uses, such as coolants for electric gadgets, car engines, heat exchangers and nuclear reactors. In this article, the authors have investigated the micropolar water‐based hybrid nanofluid containing silver and alumina nanoparticles over an extending surface.…